(untitled) (International Journal of Financial, Administrative and Economic Sciences, 2025)
This study aims to measure the impact of environmental and resource constraints on livestock development in the Kingdom of Saudi Arabia during the period 1990–2023 using econometric analysis. The results indicate that the key environmental and resource constraints affecting livestock development include climate change, animal diseases, water scarcity and its impact on the area and production of green fodder (alfalfa and Rhode’s grass), the importation and processing of feed grains (barley, maize, and sorghum), as well as loans and investments allocated to the livestock sector. The study shows that a 10% increase in fodder crop production, rainfall levels, and manufactured feed quantity leads to an increase in the number of livestock units by 4.47%, 4.46%, and 3.54%, respectively. The results also reveal an inverse relationship between green fodder production and the number of livestock units during the study period, due to the decline in the area and production of water-intensive green fodder and the gradual shift toward cultivating seasonal fodder within a period not exceeding three years. Furthermore, the number of livestock units is expected to increase from 8.01 million units in 2026 to 12.56 million units in 2030. In light of water scarcity and the decline and fluctuations in rainfall rates in sedimentary-ridge regions, the study recommends protecting livestock resources by reconsidering the loan distribution policy to increase livestock numbers in the Arabian Shield regions (Makkah, Madinah, Jazan, Al-Baha, Asir, and Najran), which are characterized by higher rainfall levels and the presence of natural rangelands.